Efficient Intelligence with Applications in Embedded Sensing - Liu, Yong; Zuo, Xingxing (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint delves into the realm of efficient intelligence, encompassing fundamental and applied research. It explores the applications of embedded sensing in a variety of embedded devices, including industrial robots, unmanned vehicles, elevator traction machines, fuel cells, and more. Special attention is given to collaborative autonomous navigation, simultaneous localization and mapping (SLAM), target object tracking, LiDAR point cloud analysis, prognostic methods for fuel cells, fabric defect detection in manufacturing, elevator traction machine recognition, object detection, vision-based autonomous forklifts, among others.